Developing a Total Quality Management (TQM) relationship model: the mediating role of organizational citizenship behavior in enhancing project performance in construction projects - Wafa Rashid, Salim Alalyani (2024)
Past literature suggested that TQM factors are likely to enhance a firm’s performance. A significant volume of existing literature has checked the relationship among TQM factors and different dimensions of performance such as quality performance, business performance and marketing success in various sectors. Therefore, there is a scarcity of literature on the impact of TQM and institutional factors in construction projects performance with respect to Omani construction industry which is facing cost overrun due to delays. This research evaluated the implementation of TQM in Oman construction sector, with a sight to minimize the structural letdown of ongoing construction projects. To obtain this objective, this study empirically examined the relationships between Total Quality Management (TQM) factors—customer focus, continuous improvement, top management commitment, project strategy, and employee involvement—and institutional factors—normative pressure and coercive pressure—on construction project performance in Oman, moderated by project governance and mediated by Organizational Citizenship Behavior (OCB). This research used positivism research philosophy and quantitative research approach to carry out this research. The population of this research were 338 ongoing construction projects in Oman. Data were collected using a self-administered survey from 216 participants engaged in ongoing construction projects. The Partial Least Squares Structural Equation Modeling (PLS-SEM) technique was utilized for data analysis. The results indicated that customer focus, project strategy, and OCB significantly influenced construction project performance, whereas continuous improvement, top management commitment, and employee involvement did not have a significant impact. Additionally, OCB partially mediated the relationship between TQM factors and construction project performance, and project governance moderated the impact of TQM on project performance. These findings offer practical implications for enhancing project performance in the construction industry and contribute theoretically to the literature on TQM factors and Institutional factors by providing empirical evidence of their effectiveness in improving construction projects’ performance in Oman.